Agricultural career training program for drop out students through work based learning / Marinah Muhammad ... [et al.] - Muhammad, Marinah; Jemali, Noor Janatun Naim; Nik Yusoff, Nik Raihan; Mohd Ghazi, Rozidaini (2021)
Agriculture is a broad field that encompasses farming, cultivation, aquaculture, and downstream industries. The agricultural sector continues to face a shortage of skilled and semi-skilled professional labour, which is generally available in most Malaysian private farms. Graduates with agricultural degrees, diplomas, and certificates from universities, polytechnics, vocational colleges, training centers, and associated departments have filled some of the roles. All such academic programs, however, require at least a SPM certificate to apply. Nevertheless, three is another source of human capital that can be trained and optimized, and they are PT3 students who dropped out in education due to low academic achievement. It is the government's role, particularly for state governments, to provide a second educational opportunity for these young people, and to lessen the societal ills associated with adolescent dropouts. Therefore, an academic program in agriculture at the certificate level, specifically for PT3 dropouts needs to be developed into a good academic product that is ready to be commercialized. Basic knowledge in the field of cultivation, livestock, and fisheries should be emphasized in this program. Students will be exposed to the concept of entrepreneurship throughout the training, whether theoretically in the classroom or practically in the field, which will be beneficial for them. Hence, they will be able to meet the high demand for employment and be able to create commercialization opportunities in agriculture. It is envisaged that through this academic program, human capital that are produced will be able to develop their own careers using agricultural expertise acquired through entrepreneurial operations, as well as give employment chances for others.